Expanding the World of Biblical Studies to Scholars Who Are Blind: Creation and Implementation of a Coptic Braille System - Smith, Daniel Charles (Near Eastern archaeology, 2024)
Until 2016, braille readers had little or no access to ancient languages beyond Hebrew, Greek, and Latin. Thus access to the study of ancient languages was difficult for blind students who needed braille texts. This article describes the history that led to the development of a braille system to represent the Coptic language. It also discusses the process of implementing the Coptic braille system in the translation of a textbook from print to braille and what was learned from the use of this braille system in the translation process. The information can provide guidance to other universities wishing to ensure access to ancient language texts for students who are blindand possible new directions for the study of this corpus.